Imperial Rome, Indian Ocean Regions and Muziris :new perspectives on maritime trade - Mathew, K. S,Ed (Manohar, 2015)
Findings deliberated in an international seminar organized in September 2013 by Institute for Research in Social Sciences and Humanities in collaboration with Archaeological Survey of India.